(untitled) (Dhaka University Journal of Business Studies, 2023)
Bangladesh is a beautiful country. She is full of tourism resources that enable to attract tourists. Among these resources, natural and man-made attractions are notable. Natural scenic beauty, cultural diversity of ethnic minority people, rivers, lakes, hills, heritage and historical sites, various religious festivals, cultural festivals, fairs etc are core tourism resources. Many fairs and festivals are celebrated in every corner of the country throughout the year. These fairs and festivals create appeal for tourists. These fairs and festivals can significantly contribute to the development of tourism industry. This paper has highlighted the prospects of fairs and festivals in the country because it has the scopes of attracting domestic and foreign tourists in these occasions. However, there are some challenges for developing fairs and festivals tourism in the country as well. The researchers have focused on some constraints and provided suggestions to overcome the challenges in terms of developing fairs and festivals for tourism purposes. Journal of Business Studies, Vol. XLII, No. 1, April 2021 Page 107-132